The Effectiveness of Waste Bank Management with Simple Accountancy in The Marga Mulya Bekasi Society - Endah Prawesti Ningrum; Novita Wahyu Setyawati (Indonesia Banking School, 2018)
Green and Clean 2017 is one of the Jakarta government’s programs to realize the city of Jakarta as a pioneer of a healthy, pollution-free city and a leading country pioneer in new breakthroughs in the field of hygiene. The management of household waste has not been well coordinated so it needs an effort to empower the community about household waste, namely the provision of counseling and technical guidance on the separation of wet and dry waste and the weighing stage until the final process where they can make a profit. Costs and benefits in the process are recorded with simple bank bookkeeping. Gradual and continuous collaboration between waste managers who have a creative, innovative, reliable and honest character with member of Family Welfare Program (Pembinaan Kesejahteraan Keluarga/PKK) in the neighborhood of RT 005 / RW 001 in Bekasi City who actively participate will create a clean, beautiful environment and increase income for people in their environment